Adapting Islamic Education in Madrasah Ibtidaiyah: Ideal Conditions in the New Normal Era - Syaiful Anam; Akhmad Nurul Kawakip; Siti Alfiyana Rahmatillah; Amrin Mustofa (AL-ISHLAH: Jurnal Pendidikan, 2024)
The Covid-19 pandemic has significantly impacted Indonesian education, prompting adaptations in teaching methods. Madrasah Ibtidaiyah institutions, in particular, shifted to online learning, facing challenges like a decline in student morals and character. This study evaluates the ideal conditions for education at the Madrasah Ibtidaiyah level in the new normal era, focusing on idealistic educational philosophy. A literature study approach was employed, analyzing data from books, academic journals, and relevant literature on idealistic educational philosophy. The aim was to explore how this philosophy can address pandemic-induced challenges and support education development in the new normal. Findings indicate that idealistic educational philosophy can effectively address post-pandemic educational challenges. This philosophy emphasizes guiding students to develop their thoughts and personalities in harmony with their intrinsic nature and societal values. Education should nurture each student's personality according to their talents, interests, and age-appropriate skills. Effective and efficient teaching methods are crucial for achieving these goals, focusing on holistic student development. The study highlights the importance of aligning educational philosophy with students' natural development. In Madrasah Ibtidaiyah, the idealistic approach enhances the moral and character development of students, adversely affected during the pandemic. By fostering individualized learning and personal growth, educational institutions can better navigate new normal challenges. Implementing idealistic educational philosophy in Madrasah Ibtidaiyah institutions can play a pivotal role in overcoming educational challenges exacerbated by the Covid-19 pandemic, ensuring well-rounded education that prepares students for their societal roles.